Implementation of New Student Admission System Policy (SPMB) at SD Inpres Perumnas - Andi Fitiah; Rahayu Rahayu; Herman Herman; Muhammad Irvan Nur'Iva (Priviet Social Sciences Journal, 2026)
This study aims to analyze the implementation of the New Student Admission System (SPMB) policy at the elementary school level and identify the challenges encountered during its implementation at SD Inpres Perumnas. Using a qualitative method with a descriptive approach, the research provides a comprehensive understanding of how the policy is applied in practice. Data were collected through observation, interviews, and documentation to obtain in-depth and contextual insights. The analysis is based on the policy implementation theory of Van Meter and Van Horn.The findings indicate that the implementation of SPMB is relatively effective, as the policy objectives and standards are realistic and aligned with the capacity of implementers and the surrounding social context. The success is supported by adequate human resources and facilities, including competent teachers, organized committees, and stable technological infrastructure. Clear organizational structure, well-defined task distribution, and effective coordination contribute to professional and efficient implementation. Positive attitudes and strong commitment from principals, teachers, and committees further enhance the process, while high parental acceptance supports policy success despite initial adaptation challenges. However, several challenges remain, including low parental digital literacy, limited access to devices and internet, and varying socio-economic conditions that influence participation.